The transformation of Russian foreign policy in light of the war in Ukraine - نبيل علي; محمد إسماعيل السعدي (Latakia University Journal - Economic and Legal Sciences Series, 2023)
Russia is considered the legitimate heir of the former Soviet Union, as it is recognized by international law as well as by the international community with that legacy, but within the geographical borders that were established after the states of the Soviet Union established their geographical borders in the United Nations. Russia would not deviate from the reality of international relations and not interfere in the affairs of states, had it not felt that its national security had become in danger, through the expansion of NATO to the countries of Russia’s immediate regional neighbors, especially in Ukraine, so Russia had to shift in its foreign policy in dealing with With the Western world in general, after it had made great and important strides of dialogue and cooperation with the West, especially after Russian President Vladimir Putin came to power, but after the great transformation in the Russian economic and political structure and its transformation towards a country with a diversified economy open to the outside world. The United States of America began to pursue policies that limit this role, by intervening in the Russian neighboring countries, and deploying advanced weapons systems that can reach the depth of Russian territory, and this is what moved Russian foreign policy from one place to another, placing national security at the top of its priorities, and searching for Restoring the status of Russia’s national strategy as a determinant and influencer in shaping the features of the international system. The Russian special military operation in Ukraine took place at the beginning of the year 2022, as an interim Russian goal aimed at removing the Western military threat, making Ukraine a neutral, disarmed country.